(untitled) (Global Business Management Review (GBMR), 2020)
In the area of the construction sector, the primary concern is economic growth. There are many issues and challenges associated with it. The growth and rapid development of this industry put their players, mainly the construction firms feeling the heat by competing with each other. The main challenge is the completion period for a particular project. This study was done in Manila, Philippines, where Design and Build (D&B) method has gained much interest and considered very important today. The rise of new innovative systems saw the emergence of new factors in the construction industry that will become future adoption. This study focuses on factors affecting the successful completion period of the construction industry, whereby it is very crucial for the country’s economic and market development. A quantitative research methodology was applied in this study. A total of 967 survey questionnaires sent out, and only 396 respondents fit to be analysed. Respondents involved were contractors, consultants, and developers. It was learned that critical success factors in project management play significant roles in driving projects to examine the determinants of success completion time of Design & Build construction projects. Findings from this study shall be used by the authority in drafting a policy guideline for future construction development. It is hoped that this study provides a better understanding of construction challenges for future undertaking.